Development of Organizational Culture in Improving the Performance of Village-Owned Enterprises in Gorontalo Regency, Indonesia - Rusli Isa; Asna Aneta; Rosman Ilato; Yanti Aneta (International Journal of Science and Society, 2022)
This research aims to determine the effect of organizational culture in improving the performance of Village-Owned Enterprises (VOEs) in Gorontalo Regency, Indonesia. Data were quantitatively collected from 114 VOE managers and analyzed using the Structural Equation Modeling (SEM) analysis tools processed with Smart PLS. The results showed that organizational culture has a positive effect of 34.3% at a significance level (α) of 0.05 on VOEs performance with a tstatistic of 4.686, which is greater than the ttable of 1.659. This implies that organizational culture has a fairly large tendency in shaping VOEs performance due to its ability to adapt to changes in the organizational environment, specifically internal adaptability. The organizational culture built in the environment needs to be maintained and enhanced by internalizing cultural values through external adaptability in the form of administration, law, politics, and economics, which will improve VOEs performance.